People's Sovereignty in the System Presidential Threshold in the Perspective Siyasah Al-Syar’iyyah - Iqbal Katrino; Yus Afrida (El-Mashlahah, 2021)
ABSTRACTUU no. 7/2017 concerning General Elections, is the legal protection for the implementation of the 2019 General Election using the system presidential threshold. The problem is, this is seen as castration of individual rights where power is in the hands of the people. Equal treatment before the law and politics in the context of nominating the President and Vice President is limited to parties that are part of and meet the threshold in the 2014 general election. This research found that the implementation of the system Presidential Threshold in Indonesia was an embodiment of the people's sovereignty itself. Where the individual directly determines the leader, and in making the requirements to become a leader, and the DPR is a representation of the people. This eliminates concerns in the community when the system will be ratified Presidential Threshold in Law Number 7 of 2017 concerning Elections so that the people's sovereignty in the threshold system is by siyasah syar’iyyah where ahlul halli wa al-‘aqdi can determine candidate leaders and Bai’ah is a form of the general election in determining the leader.Keywords: People’s Sovereignty, Presidential Threshold, Siyasah al-Syar’iyyah.\ABSTRAKUU No. 7 /2017 tentang Pemilihan Umum dasar hukum dilaksanakannya Pilkada Umum Tahun 2019 dengan menggunakan system presidential threshold. Persoalannya adalah, hal ini dipandang sebagai pengebirian hak-hak individu dimana kekuasaan berada di tangan rakyat. Perlakuan yang setara di depan hukum dan politik dalam rangka mencalonkan Presiden dan Wakil Presiden menjadi terbatas hanya pada partai yang menjadi bagian dan mencukupi -threshold di pemilihan umum 2014. Riset ini menjumpai bahwa pelaksanaan sistem Presidential Threshold di Indonesia merupakan perwujudan dari kedaulatan rakyat itu sendiri. Di mana individu secara langsung menentukan pemimpin, dan dalam pembuatan persyaratan untuk menjadi pemimpin, yang mana DPR adalah representasi dari rakyat. Hal ini menghapuskan kekhawatiran di masyarakat ketika akan disahkannya sistem Presidential Threshold dalam Undang-Undang Nomor 7 Tahun 2017 tentang Pemilu, sehingga kedaulatan rakyat dalam sistem ambang batas sudah sesuai dengan siyasah syar’iyyah dimana ahlul halli wa al-‘aqdi memiliki kapasitas untuk menentukan calon permimpin dan Bai’ah adalah bentuk dari pemilihan umum dalam menentukan pemimpin.Kata Kunci: Kedaulatan Rakyat, Presidential Threshold, Siyasah Syar’iyyah.